Asymmetrical dimethylarginine inhibits shear stress-induced nitric oxide release and dilation and elicits superoxide-mediated increase in arteriolar tone. - Toth, J; Racz, A; Kaminski, P; Wolin, MS; Bagi, Z; Koller, A (2007)
l-arginine is the substrate used by NO synthase to produce the vasodilator NO. However, in several human diseases, such as hyperhomocysteinemia, diabetes mellitus, and hypertension, there is an increase in serum levels of methylated l-arginines, such as asymmetrical dimethylarginine (ADMA), which cannot be used by NO synthase to produce NO. Yet, the functional consequence of increased levels of ADMA on the vasomotor function of resistance vessels has not been delineated. We hypothesized that elevated levels of exogenous ADMA inhibit NO mediation of flow/shear stress-dependent dilation of isolated arterioles. In the presence of indomethacin, isolated arterioles from rat gracilis muscle (approximately 165 microm at 80 mm Hg) were incubated with ADMA (10(-4) mol/L), which eliminated the dilations to increases in intraluminal flow (control: from 164+/-5.4 to 188+/-3.8 microm versus ADMA: from 171+/-6.1 to 173+/-6.3 microm at 20 microL/min). ADMA did not affect dilations to nifedipine (10(-6) mol/L; control: 63.4+/-2%, ADMA: 65.8+/-3%) or 8-bromo cGMP (10(-4) mol/L; control: 51.2+/-2.1%, ADMA: 49.3+/-3.4%). In addition, ADMA elicited significant constriction of arterioles (from 173+/-17 microm to 138+/-16 microm at 80 mm Hg), which was prevented by previous incubation of arterioles with polyethylene-glycol (PEG) superoxide dismutase (SOD; 120 U/mL, control: 155+/-11 microm versus ADMA: 150+/-14 microm). Correspondingly, ADMA increased PEG-SOD reversible manner the production of vascular superoxide assessed by lucigenin-enhanced chemiluminescence and ethidium bromide fluorescence. Thus, increased levels of ADMA in various diseases could inhibit the regulation of arteriolar resistance by shear stress-induced release of NO and elicit superoxide-mediated increase in basal tone, both of which favor the development of hypertension.